Potential of remote sensing techniques for integrated spatio-temporal monitoring and analysis of drought in the Sana River basin, Bosnia and Herzegovina - Sabljić, Luka; Lukić, Tin; Marković, Slobodan B.; Bajić, Davorin (Időjárás, 2024)
The subject of the research paper is the exploration of the potential of remote sensing techniques for enhanced spatio-temporal monitoring and analysis of drought impacts within the Sana River basin area in Bosnia and Herzegovina (B&H). The aim is to identify meteorological, hydrological, agricultural, and socio-economic drought occurrences by processing remote sensing “products”. An integral part of this aim involves calculating the standardized precipitation index (SPI), temperature condition index (TCI), vegetation condition index (VCI), and vegetation health index (VHI). Meteorological drought monitoring was carried out using the Climate Hazards Group InfraRed Precipitation with Station Data (CHIRPS) dataset processed through the Google Earth Engine (GEE) platform. A 42-year period (1981–2023) was compared with reference years (2016 and 2017). The occurrence of meteorological drought (lack of precipitation) was identified, and SPI was calculated. The period with reduced precipitation and negative SPI values during 2016 and 2017 coincided with the pattern of decreasing water levels in the main stream of the Sana River, confirming the impact of meteorological drought on the occurrence of hydrological drought. Agricultural drought monitoring was conducted using Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data, namely MOD13Q1 and MOD11A2, to calculate TCI, VCI, and VHI. The results indicate negligible drought occurrence for 2016, while extreme agricultural drought was observed in the basin area for 2017. The consequences of agricultural drought on the occurrence of socioeconomic drought were examined. The results show an extreme decrease in yields of wheat, barley, corn, potatoes, pears, and plums during 2017 compared to 2016. The research contributes to a better spatio-temporal understanding of drought phenomena, and the presented data and results are significant for numerous practical issues related to monitoring, mitigation, and/or prevention of negative consequences of drought in river basin areas.